Steel frame assembly robot / Nur Syarfa binti Romli and Zulkifli bin Ab Halim - Romli, Nur Syarfa; Ab Halim, Zulkifli (2019)
At present, the Industrial Revolution 4.0 emerges and changes the minds of many community on the implementation of new and sophisticated technologies, especially in the construction industry. Industrialized Building System (IBS) is one of the elements in construction that provide high technology and one example of IBS is steel frame system. However, there are few problems still happen during the process of installation steel frame system. Therefore, a study has been conducted to identify problems in the current method of installing steel frame system. Next, to determine the various methods and innovation approaches on technologies used from the past up to now and lastly, to propose an innovation idea to cater all the problems. This study was started out by doing desk study from articles, books and journals. Then, data collection also has been employed by assembling the components of innovation idea and also make simulation. Overall, this innovation idea is hoped to be accepted in the construction industry as it has a very high impact on the industry especially regarding its performance to the overall process of steel frame installation.